Computational propaganda in Canada: The use of political bots - McKelvey, F; Dubois, E (Computational Propaganda Project, 2017)
Are bots active in Canada? Yes. Are they influential? Maybe. Using a combination of quantitative social media analysis, content analysis of news articles and qualitative interviews, we study the use of political bots in Canada. We identify four kinds of bots. Amplifiers game digital systems to promote a message or channel. Dampeners supress and remove information online. Alongside these problematic bots, we also find a number of benign bots that help journalists, civil society and governments. These bots include transparency bots that disclose information to the public and servant bots that help maintain services and infrastructures. Even though bots might not yet be influential in Canada, improved media literacy and increased public discussion of the pitfalls of social media are required.